Internet Addiction among Secondary School Students and Their Awareness of Its Psychosocial Consequences - Roaa Alkahazraji; Amean A Yasir (Kufa Journal for Nursing Sciences)
Background: The Internet has become an essential part of modern life, used by a large number of people of all ages, especially teenagers. Therefore, the number of its users around the world is increasing daily, exposing some to its negative effects such as Internet addiction (I.A.). Internet Addiction is the frequent and reckless use of electronic devices, which may be present for a long time when engaging in non-work-related activities which can lead to physical, social, psychological, and academic problems.